2018
DOI: 10.3847/1538-4357/aaccf5
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Model-independent Masses and Radii of Single-lined Eclipsing Binaries: Analytic Precision Estimates

Abstract: We derive analytic estimates for the ability with which one can obtain precise, empirical stellar masses and radii via single-lined eclipsing binaries (EBs) in the era of Gaia and TESS. Including stars that host transiting substellar companions, such single-lined EBs already number in the hundreds from ground-based transit surveys and will comprise a major component of the science yield from the upcoming TESS mission. We explore the requirements for obtaining a given fractional precision on the masses and radi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 101 publications
0
37
1
Order By: Relevance
“…As we demonstrate in this paper, it is necessary to re-fit all of the data for each system, including the parallax constraints, to take full advantage of the available information, and achieve higher precision. Significant improvements in stellar and planetary parameters when incorporating parallax measurements have also been reported for the system KELT-11 (Beatty et al 2017) and for several M dwarfs with planets observed by Kepler (Stevens et al 2018). These works differ from the approach presented here in that they focused on measuring empirical stellar masses and radii, without relying on stellar evolution models.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…As we demonstrate in this paper, it is necessary to re-fit all of the data for each system, including the parallax constraints, to take full advantage of the available information, and achieve higher precision. Significant improvements in stellar and planetary parameters when incorporating parallax measurements have also been reported for the system KELT-11 (Beatty et al 2017) and for several M dwarfs with planets observed by Kepler (Stevens et al 2018). These works differ from the approach presented here in that they focused on measuring empirical stellar masses and radii, without relying on stellar evolution models.…”
Section: Introductionmentioning
confidence: 85%
“…Using Gaia Stevens et al (2018) derived analytical estimates of uncertainties for stellar mass and radii in the current era where TESS and Gaia data are available. We compare our uncertainties in the PARSEC Empirical results (e=0) in this work to the analytic estimates based upon Equations 50-53 in their paper.…”
Section: Comparison With Analytically Predicted Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead it serves more as an effective surface gravity assuming a spherical star. Under this assumption, Section 2.3.1 of Stevens et al 2018 presents a derivation of system parameters from spectroscopic stellar RV semi-amplitude and spectroscopic stellar surface gravity. This constraint is the weakest because it does not account for the oblate geometry of the star.…”
Section: Complementary Constraints On System Parametersmentioning
confidence: 99%
“…Newton's fundamental law of gravitation can be combined with knowledge of the system's orbital motion to recover the dynamical masses of both stars purely empirically. These measurements calibrate the stellar evolution models that are typically used to determine the masses of stars and indirectly the planets they host (Popper 1980;Harmanec 1988;Andersen 1991;Torres et al 2010;Stevens et al 2018).…”
Section: Introductionmentioning
confidence: 99%